Effect of temperature and curing on the early hydration of cementitious materials - Siddiqui, Md Sarwar (Kansas State University, 2010)
Concrete is the most widely used construction material. Concrete strength and durability develop from a series of exothermic reactions involving water called hydration. Long-term durability and performance of concrete is very much dependent on the early hydration behavior of cementitious materials. This study examined the effects of curing temperature and access to moisture on the early age reaction rate of cementitious materials, and methods for quantifying these effects. Apparent activation energy (Ea) relates the effects of temperature on the cement hydration reaction. There are various methods and calculation techniques for estimating Ea that result in greatly varying values. Cement paste and mortar are often used to calculate Ea and used later for concrete. Ea values were calculated using cement mortar and paste by isothermal calorimetry and showed excellent correlation. This validates the use of Ea based on cement paste in modeling concrete behavior. Ea values were also calculated by chemical shrinkage and it showed potential for use in calculating Ea. Cementitious materials need free water to be available for hydration to continue. Curing with either waxy curing compounds or ponded water are common practices. The thickness of distilled water, lime-saturated water, and cement pore water used as a curing method affects the rate of hydration. Water-cementitious material ratio (w/cm) and sample depth affect the performance of water curing, with low w/cm being the most significant. Partial replacement of sand by fine lightweight aggregate also improves the hydration of cementitious material much more than conventional water ponding. Curing compounds showed improvements in cement hydration compared to uncured samples.
Keywords: Cementitious material; Hydration; Apparent activation energy; Effect of Curing; Effect of temperature; Engineering, Civil (0543)